Clinical trial designs and models for analgesic medications for acute pain in neonates, infants, toddlers, children, and adolescents: ACTTION recommendations. Issue 2 (February 2018) - Walco, Gary A.; Kopecky, Ernest A.; Weisman, Steven J.; Stinson, Jennifer; Stevens, Bonnie; Desjardins, Paul J.; Berde, Charles B.; Krane, Elliot J.; Anand, Kanwaljeet J.S.; Yaster, Myron; Dampier, Carlton D.; Dworkin, Robert H.; et al.
Abstract : Abstract: Clinical trials to test the safety and efficacy of analgesics across all pediatric age cohorts are needed to avoid inappropriate extrapolation of adult data to children. However, the selection of acute pain models and trial design attributes to maximize assay sensitivity, by pediatric age cohort, remains problematic. Acute pain models used for drug treatment trials in adults are not directly applicable to the pediatric age cohorts–neonates, infants, toddlers, children, and adolescents. Developmental maturation of metabolic enzymes in infants and children must be taken into consideration when designing trials to test analgesic treatments for acute pain. Assessment tools based on the levels of cognitive maturation and behavioral repertoire must be selected as outcome measures. Models and designs of clinical trials of analgesic medications used in the treatment of acute pain in neonates, infants, toddlers, children, and adolescents were reviewed and discussed at an Analgesic, Anesthetic, and Addiction Clinical Trial Translations, Innovations, Opportunities, and Networks (ACTTION) Pediatric Pain Research Consortium consensus meeting. Based on extensive reviews and continuing discussions, the authors recommend a number of acute pain clinical trial models and design attributes that have the potential to improve the study of analgesic medications in pediatric populations. Recommendations are also provided regarding additional research needed to support the use of other acute pain models across pediatric age cohorts.